Laminate veneer ceramics in aesthetic rehabilitation of teeth with fluorosis: a 10-year follow-up study - Zeynep Basagaoglu Demirekin; Suha Turkaslan (BMC, 2022)
Abstract Background Fluorosis is one of the color anomalies seen in teeth. White lines and blurred areas associated with mild fluorosis are barely noticeable; in its severe form, tooth enamel surface changes ranging from staining and pitting may be observed. The treatment of fluorosis not only provides aesthetic and functional correction but also helps to improve the patient's self-esteem. Methods The present retrospective study evaluated the clinical quality, success rate, and estimated survival of porcelain laminate veneers in teeth with anterior fluorosis. Three hundred fifty-eight porcelain laminate veneers (254 in the anterior maxilla and 104 in the mandible) were "functional" restorations that covered the incisal edge and part of the palatal/lingual side of the tooth with a 1 mm high palatal bevel. Ceramic veneers were fabricated with lithium disilicate reinforced glass-ceramic material (IPS e.max Press, Ivoclar Vivadent, Schaan, Liechtenstein). The modified United States Public Health Service criteria were used for clinical evaluation of the restorations. Results On the basis of these criteria, marginal adaptation, color match, marginal discoloration, surface roughness, restoration fracture, tooth fracture, restoration wear, antagonist tooth wear, caries and postoperative sensitivity were evaluated yearly. The survival rate in the current study was ≥ 0.997 for 10 years. Conclusions The results of this clinical study should encourage clinicians to consider ceramic veneers over crown restorations when restoring the smile of patients with advanced fluorosis.